Transformasi Kurikulum K-13 ke Kurikulum Merdeka Berbasis Quality Function Deployment (QFD) - Hufri; Wahab (Kariman: Jurnal Pendidikan Keislaman, 2026)
This study aims to analyze the transformation of curriculum policy from the 2013 Curriculum (K-13) to the Quality Function Deployment (QFD)-based Independent Curriculum at MA Raudlatul Firdaus, focusing on how student needs are translated into a more responsive and quality-based curriculum design. This study uses a qualitative approach within an educational management framework, with data collection techniques through in-depth interviews, participant observation, and documentation studies of teachers and students as key informants. Data analysis is carried out systematically through reduction, presentation, and conclusions, and is strengthened by a QFD approach through the House of Quality instrument to connect the voice of customers with technical learning needs. The results show that the implementation of QFD can produce a more flexible, contextual, and student-centered curriculum, as well as increasing student engagement, learning effectiveness, and the quality of data-driven curriculum planning. In addition, key student needs such as project-based learning, instructional differentiation, and assessment formats are translated into operational technical strategies. The novelty of this study lies in the integration of QFD in the analysis of curriculum policy transformation in Islamic educational institutions, which has so far been more widely applied in the industrial sector. This approach offers a new perspective by positioning students as “customers” of education, so that the development curriculum becomes more systematic, adaptive, and oriented to real needs, while strengthening the data-based and sustainable education quality assurance system.